Dynamic Transcriptional Events in Distal Sural Nerve Revealed by Transcriptome Analysis - Hong, Young Bin; Jung, Sung-Chul; Lee, Jinho; Moon, Heui-Soo; Chung, Ki Wha; Choi, Byung-Ok (Experimental neurobiology, 2014)
Compared with biochemical information available about the diseases in the central nervous system, that for peripheral neuropathy is quite limited primarily due to the difficulties in obtaining samples. Characterization of the core pathology is a prerequisite to the development of personalized medicine for genetically heterogeneous diseases, such as hereditary motor and sensory neuropathy (HMSN). Here, we first documented the transcriptome profile of distal sural nerve obtained from HMSN patients. RNA-seq analysis revealed that over 12,000 genes are expressed in distal sural nerve. Among them 4,000 transcripts are novel and 10 fusion genes per sample were observed. Comparing dataset from whole exome sequencing revealed that over 1,500 transcriptional base modifications occur during transcription. These data implicate that dynamic alterations are generated when genetic information are transitioned in distal sural nerve. Although, we could not find significant alterations associated with HMSN, these data might provide crucial information about the pathophysiology of HMSN. Therefore, next step in the development of therapeutic strategy for HMSN might be unveiling biochemical and biophysical abnormalities derived from those potent variation.